English and Its Difficulties: An Analysis of Student Responses - Sahid, Suardi; Murianty, Riana; Manilet, Badaria (Universitas Islam Ahmad Dahlan (UIAD), 2024)
The purpose of this study was to determine the difficulties in learning English on the eighth-grade students at Advent Junior High School Manokwari. The research design utilized, a mixed-method design to identify students' difficulties and how students overcome the difficulties when learning English. There were 21 students as participants obtained using purposive sampling technique. The place of this research was Junior High School of Advent Manokwari. The research data were collected through survey and interview using questionnaire and a list of questions as instrument. The collected data were analyzed using percentage, descriptive statistic and content analysis. The finding shows that based on the mean score, most of the students had a positive enough perspective that learning English is difficult. The result of questionnaire was also confirmed by the result of interview that the students’ faced difficulties in learning English, due to the lack of inspiration to learn English, difficult to pronounce English word, feel shy about speaking English, fear of making a mistake, lack of English vocabulary, do not know meaning in English conversation, and students cannot arrange English words to make sentences. This study will help the teacher in understanding how students overcome their difficulties when they learn English and in finding effective ways of learning to deal with the problems that students face.